Gambaran Pengetahuan Ibu Pemulung Tentang ISPA Pada Balita di wilayah Kerja Puskesmas Tamangapa - Intan Nursiani; Rini Fitriani; Arlina Wiyata Gama (Celebes Health Journal, 2020)
Acute respiratory infections (ARI) is an infection that attacks the upper and lower respiratory tract that lasts approximately 7-14 days. Recorded cases of ARI in Indonesia as much as 503,738 in toddlers with a major visit in Puskesmas (40%-60%) and at the hospital (15%-39) with visits of acute respiratory infections in Tamangapa puskesmas each year has increased namely 2014 (77%), 2015 (80%), 2016 (82%), 2017 (83%), 2018 (85.7%), in 2019 which in data until August 79%. The research aims to figure out the knowledge of the purview of acute respiratory infections in infants. This research is a descriptive study. The sample number is 66 respondents using the Purposive Sampling Non Random Sampling technique. Research was conducted in Tamangapa's work area Puskesmas on January until February. Analyzed using univariate analysis. From the research results obtained by the knowledge of a scavenger mother about the etiology of ISPA in infants is good (51.5%). The knowledge of risk factors that can trigger ARI disease in infants is good (56.1%). Knowledge of ISPA clinics symptoms in infants is sufficient (45.5%). ARI disease prevention Knowledge in good toddlers (48.5%). General knowledge of scavenger mothers about ARI disease in infants is good (47.0%).The conclusion of this research is an knowledge of scavenger mothers of having a toddler in the working area of ​​the Tamangapa Puskesmas was generally good.